KAJIAN INTERAKSI OBAT PADA PASIEN PENYAKIT GAGAL JANTUNG RAWAT INAP DI RUMAH SAKIT UMUM DAERAH TUGUREJO SEMARANG TAHUN 2008 - Yulias Ninik Windriyati; Erwin Tukuru; Ibrahim Arifin (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2010)
ABSTRACT Heart failure is a pathological conditions such as abnormal heart function so that the heart can not pump blood to meet the metabolic needs of the tissues. Heart failure patients in general should be given at least four types of treatment that is, ACE inhibitors (angiotensin converting enzyme), diuretics, β- blockers, and digoxin. Providing a variety of drugs can cause drug interactions. This study aimed to verify the incidence of drug interaction in heart failure patients hospitalized in the Regional General Hospital Tugurejo Semarang. The data were collected retrospectively to medical record data in general hospital Tugurejo Semarang. Data were analyzed with descriptive non-analytic methods using Drug Interaction Facts (Tatro 2007) as a reference standard. The results of this research showed that of 90 patients who potential experience drug interactions 63 patients (70%). There are 43 cases (29.05%) of pharmacokinetic interaction, 47 cases (31.76%) of pharmacodynamic interactions and unknown mechanisms of interaction 58 cases (39.19%). Based on the level of significance there are three types of interactions have level of significance 1 (12.5%), there are 5 types of interactions have level of significance 2 (20.83%), and 3 types of interactions have level of significance 3 (12.5%), for level of significance 4 there are 6 types of interactions (25%), and 7 types of interactions with the level of significance 5 (29.17%). Drug interactions that have the highest incidence of occurrence is captopril and acetosal (33 cases), digoxin and captopril (19 cases). Key words : drug interaction, heart failure